(untitled) (Research, Society and Development, 2022)
The problems faced by public managers in the health area range from the limitation of public resources to the high demand of society for the services provided by the Unified Health System (SUS), which recommends that these managers value efficiency in the use of resources. In this context, this study seeks to measure the technical efficiency scores and the scale of health expenditures in 1694 municipalities in the Northeast and to identify the determinants of this efficiency. For this, the Data Envelopment Analysis (DEA) model and the quantile regression model were used, using secondary data having 2019 as the base year. The main results show that few municipalities are at a fully efficient level and that most of them are in the class between 0.50 and 0.75 efficiency level. From the quantile regression, it is noted that there are socioeconomic and demographic factors that are associated with different levels of efficiency. A relevant fact is that the municipality that spent the most on health per inhabitant had the lowest efficiency score, in the DEA model with constant returns to scale. This indicates that higher expenditures are not necessarily associated with higher efficiency scores.